Private Earnings Guidance and Its Implications for Disclosure Regulation - Wang, Isabel Yanyan (The Accounting Review, 2007)
This study investigates three related questions: (1) Why did some firms provide private earnings guidance to analysts before Regulation Fair Disclosure? (2) How did the exogenous shock of Regulation Fair Disclosure affect these firms' disclosure policies? (3) What are the economic consequences of this disclosure regulation? To address these questions, I develop a new measure of private earnings guidance. Consistent with theory, I find that firms were more likely to provide private earnings guidance if they had higher proprietary information costs, and if their earnings were more predictive of other firms' earnings. Policymakers enacted Regulation Fair Disclosure to stop private earnings guidance, but they also intended for managers to replace private earnings guidance with public earnings guidance, thereby improving the information environment. However, I find that roughly half of the firms that I classify as relying more on private earnings guidance replace private earnings guidance with non-disclosure instead of public earnings guidance, and as a result, these firms suffer significant deterioration in their information environments. Consistent with theory, firms are more likely to replace private earnings guidance with nondisclosure if they have lower information asymmetry and higher proprietary information costs. On the other hand, firms that replace private earnings guidance with public earnings guidance, on average, prevent significant deterioration in their information environments. Evidence that firms respond to disclosure regulation as predicted by theory can help policymakers anticipate which firms' information environments are likely to be adversely affected by new disclosure regulations.